‘We’ share but ‘They’ cheat: student qualitative perspectives on cheating in higher education - Rowena Harper; Felicity Prentice (International Journal for Educational Integrity)
Abstract This paper addresses the marked absence of student voices in contemporary research on academic integrity, and in doing so challenges a number of persistent ideas about cheating in higher education. We report the qualitative findings from a large-scale survey of Australian university students (n = 14,086), in which 4,915 students responded to one open-text item: ‘Is there anything else you want to tell us about cheating in higher education?’. Responses indicated that the survey’s focus on ‘contract cheating’ was misdirected, reporting that other forms of cheating are far more prevalent and accepted as behavioural and ethical norms. Most critically, responses articulated a ‘we’ group (domestic students) and a ‘they’ group (international students) and their behaviours – while similar – were judged differently. The ‘we’ group described their participation in a social economy of assessment, through which students share assignments and work together to ‘help each other’. The ‘they’ group, in contrast, were described as outsourcing assignments and relying on others to ‘probably cheat’. Evidence of othering and double standards reflected a racist discourse, and indicated a potential relationship between the social and academic exclusion of international students in Australia and commercial contract cheating, the scandalisation of which we aim to challenge in this paper.